Addictions : a comprehensive guidebook - McCrady, Barbara S.; Epstein, Elizabeth E. (Oxford University Press, 1999)
Part I. Epidemiology, Etiology, and Course of Substance Use Disorders. 1. Alcohol and Drug Use, Abuse, and Dependence: Classification, Prevalence, and Comorbidity, Bridget F. Grant and Deborah A. Dawson. 2. The Course of Untreated and Treated Substance Use Disorders: Remission and Resolution, Relapse and Mortality, John W. Finney, Rudolf H. Moos, and Christine Timko. 3. Theories of Etiology of Alcohol and Other Drug Use Disorders, Michie N. Hesselbrock, Victor M. Hesselbrock, and Elizabeth E. Epstein. Part II. Specific Drugs of Abuse: Pharmacological and Clinical Aspects. 4. Alcohol, Darlene M.